Using Instructional Scaffolding in hybrid learning environment: A critical Review - Dina Ayman; Mahmoud Mohaseb; Jehan El-Bassuony (Port Said Journal of Educational Research)
Instructional Scaffolding is a constructive strategy that helps learners to do activities and tasks with the assistance or support of an expert. It is not confined only to the information that should be acquired; it also calls for social interaction between the learner and the expert. Thus, learning environments are one of the most significant responsibilities that the teachers should develop to engage and motivate their learners. One of these learning environments is hybrid learning environment. The paper addresses the instructional scaffolding strategies and the course plan of hybrid learning environment. This paper's purpose is to provide an overview of a recent research on hybrid learning environment, instructional scaffolding and discuss the implications of the research for language instruction. The discussion presents definition of instructional scaffolding, characteristics of instructional scaffolding, instructional scaffolding strategies, and features of instructional scaffolding. In addition, the paper highlights the definition of hybrid learning environment, the plan course of hybrid learning environment, and its role in relation to instructional scaffolding.